2005
DOI: 10.1001/archinte.165.17.1970
|View full text |Cite
|
Sign up to set email alerts
|

International Differences in End-of-Life Attitudes in the Intensive Care Unit

Abstract: In countries where intensive care medicine is relatively well developed, considerable differences remain in physicians' attitudes toward end-of-life care in the intensive care unit. Substantial work remains if an international consensus on these issues is to be reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
2
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 29 publications
7
126
2
12
Order By: Relevance
“…(29) Probably due to this shortcoming in the legislation and to cultural issues, Brazilian physicians prefer to give verbal and informal orders not to resuscitate. (30) However, Deheinzelin (18) states that the verbal do-not-resuscitate order may conflict with Bioethical principles, regarding the patient's autonomy. These principles define that every human being has the right to be informed about the therapeutic modes available for his clinical situation and about the prognosis of his disease.…”
Section: Discussionmentioning
confidence: 99%
“…(29) Probably due to this shortcoming in the legislation and to cultural issues, Brazilian physicians prefer to give verbal and informal orders not to resuscitate. (30) However, Deheinzelin (18) states that the verbal do-not-resuscitate order may conflict with Bioethical principles, regarding the patient's autonomy. These principles define that every human being has the right to be informed about the therapeutic modes available for his clinical situation and about the prognosis of his disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several different studies [14][15][16][17][18][19] have demonstrated marked differences not just between different regions on the planet, but also within each country, even in the same city. 20,21 These differences exist in all phases of the LSL decision: from the initial process to its conclusions, ending with the withdrawal or withholding of life support treatment.…”
Section: Differences Between Countriesmentioning
confidence: 99%
“…The interval between decision and action taken is 30 minutes, which is much lower than interval described in European countries, which is 2 days. 17,18,20 The reason for this may be the way in which the decision is taken. In the USA, when a decision is taken to suspend treatment, the doctors immediately take this action in the presence of the family.…”
Section: Differences Between Countriesmentioning
confidence: 99%
“…Health care policies, available resources, and societal consensus on the management approach would also impact on the clinical decisions of withdrawing or withholding treatment for severely sick patients [8,2124]. We therefore undertook this survey to explore the renal physicians’ practices of withholding and withdrawal of dialysis treatment during provision of renal care at end-of-life for patients with ESKD in UAE.…”
Section: Introductionmentioning
confidence: 99%